Intervensi Edukasi Berbasis Video dan Leaflet untuk Mengubah Perilaku Merokok Remaja - Anisa Kurniawati; Hendawati Hendawati; Faiza Yuniati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Smoking behavior among adolescents is a serious public health concern and contributes to an increased risk of degenerative diseases. Health education using educational media is considered effective in enhancing knowledge and modifying adolescent behavior. This study aimed to evaluate the effect of health education through animated video and leaflet media on junior high school students’ knowledge, attitudes, and practices regarding the dangers of smoking. A quasi-experimental one-group pretest-posttest design was conducted with 100 randomly selected junior high school students in Palembang City. The intervention included educational animated videos and distribution of leaflets. Pretest and posttest measurements were conducted using structured questionnaires. Data were analyzed using the Wilcoxon Signed Rank Test. There were significant increases in the mean scores of knowledge (from 6.34 to 9.20), attitudes (from 40.24 to 45.66), and practices (from 20.80 to 23.82), with p=0.000 for all variables. Health education using animated videos and leaflets is effective in improving student knowledge and shaping positive behavior in smoking prevention. This approach is recommended as part of school-based health promotion strategies.